Factors for the implementation of the circular economy in Big Data environments in service companies in post pandemic times of COVID-19: The case of Colombia - Almanza Junco, Carlos Alberto; Pulido Ramirez, Marial del Pilar; Gaitán Angulo, Mercedes; Gómez-Caicedo, Melva Inés; Mercado Suárez, Álvaro Luis (Frontiers in Big Data, 2023)
In emerging economies, Big Data (BD) analytics has become increasingly popular, especially in light of its opportunities and expected benefits. Such analyses have identified that the production and consumption of goods and services, although unavoidable, have proven to be unsustainable and inefficient. Therefore, the concept of the circular economy has strongly emerged as a sustainable approach that contributes to the eco-efficient use of resources and can make both the economy and modern life thrive. However, in order to develop a circular economy in Big Data environments, it is necessary to understand what factors influence the intention to accept implementation. Based on the theory of planned behaviour and a Partial Least Squares Structural Equation Model (PLS-SEM), the current research assesses the influence of attitudes, subjective norms and perceived behavioural norms on the intention towards adopting the circular economy in environments mediated by Big Data analytics. A total of 413 service SMEs based in Colombia participated in an online survey. The results show that managers' attitudes, subjective norms and perceived behavioural norms positively influence organisations' intentions to implement circular economy best practices. In addition, organisations' intentions positively influence the adoption of Big Data. The study also shows that most organisations have positive intentions towards Big Data and the circular economy; however, they perceive lack of government support and cultural barriers as the main constraint to adoption. This information can help companies develop strategies to move towards a circular economy and provide governments with relevant information on the current state of implementation of this type of economy and generate new strategies for further implementation.